Status anak di luar nikah: komparasi hukum Islam dan hukum positif - Afkarina, Iza; Nur Khotibul Umam, M. (AL-MUQARANAH, 2024)
One of the legal consequences of the status of a child out of wedlock is the status (position) of the child out of wedlock. In Indonesian legislation, there are several laws that explain the status of children out of wedlock, although there are differences in the law and status of these children between these laws. In Islamic law, children out of wedlock have a different position from legitimate children, biological children, adopted children, and children resulting from adultery. The existence of this position affects in determining guardianship, nasab, inheritance and hadhanah. This research uses a normative study approach, namely comparing the status of adopted children according to Islamic law and positive law. This research is a type of Library Research (literature), the author will present library data in the form of books, journals, research reports, papers and other library materials that are accurate to the object of the subject matter. Based on the results of the research conducted, it can be concluded that, the status of children outside of marriage based on Islamic law is not the same as biological children, and legal children in Islamic law the status of children outside of marriage in terms of nasab, remains with the mother and her mother's family. According to positive law, Constitutional Court Decision Number 46/PUU-VIII/2010 stipulates that the status of children out of wedlock can only be related to the mother and her family, unless there is recognition from a biological father who can be proven scientifically and technologically. This is different from Constitutional Court Decision Number 43/PUU-VIII/2010 which regulates other aspects of children's rights. This is because the status of extramarital children is only dinasabkan to the mother and the mother's family, so directly from the Constitutional Court's decision stipulates that the position or nasab of extramarital children (either due to adultery or nikah sirri) is to their biological father who can be proven by science and technology.